Lenvatinib for thyroid cancer treatment: discovery, pre-clinical development and clinical application. (2nd January 2020) - Paragliola, Rosa Maria; Corsello, Andrea; Del Gatto, Valeria; Papi, Giampaolo; Pontecorvi, Alfredo; Corsello, Salvatore Maria
ABSTRACT: Introduction : About one third of patients affected with thyroid cancer present with recurrent disease. Unresectability, advanced disease and radioiodine refractoriness are considered poor prognostic factors. Treatment with small molecules inhibiting molecular signaling can be considered for patients with progressive disease, when other therapeutic strategies cannot be applied. Lenvatinib is a tyrosine kinase inhibitor targeting multiple molecular factors involved in angiogenesis and tumor progression. Preclinical studies have demonstrated the utility of lenvatinib as a targeted therapy for different tumors, including both differentiated and anaplastic thyroid cancer. Areas covered : The authors provide an overview of the preclinical development of lenvatinib in the treatment of thyroid cancer and review its clinical application. They also provide their expert opinion on its development. Expert opinion : Preclinical studies have helped in the understanding of the mechanisms of thyroid carcinogenesis and in the development of a targeted therapy. These findings have represented the rationale for the use of lenvatinib in clinical trials, which have confirmed its utility but yet failed to prove a clear benefit in overall survival. The decision to start a systemic treatment with lenvatinib must be personalized for each patient evaluating the risk/benefits ratio. Treatment emergent adverse events must be considered and reasonably managed by a multidisciplinary approach.